Leveraging sequential deep learning models for detecting multitude of human action categories - Pranta, Kazi Al Refat; Islam, Fahad Mohammad Rejwanul; Ahmed, Khandakar Fahim; Saha, Prince; Rahman, Naimur (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.